2018
DOI: 10.1007/s10096-018-3377-5
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory automation reduces time to report of positive blood cultures and improves management of patients with bloodstream infection

Abstract: The impact on time to results (TTR) and clinical decisions was evaluated for mono-microbial positive blood cultures (BC) processed using the BD Kiestra Work Cell Automation (WCA) system. Positive BC were processed by the WCA system by full-automatic subculture on solid media and digital imaging after 8 h of incubation (8-h method) followed by identification (ID) and antimicrobial susceptibility testing (AST). To evaluate the accuracy of the 8-h method, ID and AST from 8-h and overnight incubated colonies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Equally important may be the fact that for some of the special specimens, classical technologies have to be maintained. Still, the opportunities in the automation field are considered revolutionary by many (36,73,74). For these reasons, modularity and scalability (e.g., integration of multiple incubation/imaging systems, free-standing inoculators, incubators, culture plate processing systems, and integrated workstations) become important design considerations for manufacturers, such that a laboratory of any size would have access to components of the complete system.…”
Section: Do Microbiology Laboratories Benefit From Automation?mentioning
confidence: 99%
“…Equally important may be the fact that for some of the special specimens, classical technologies have to be maintained. Still, the opportunities in the automation field are considered revolutionary by many (36,73,74). For these reasons, modularity and scalability (e.g., integration of multiple incubation/imaging systems, free-standing inoculators, incubators, culture plate processing systems, and integrated workstations) become important design considerations for manufacturers, such that a laboratory of any size would have access to components of the complete system.…”
Section: Do Microbiology Laboratories Benefit From Automation?mentioning
confidence: 99%
“…De Socio and co-workers evaluated the effect of an automated workflow on the time to report for mono-microbial positive blood cultures [31]. In their setting the time to report was reduced by 24 h and the duration of empirical therapy (in contrast to evidence/AST-based therapy) was reduced by 32 h. The 30-day crude mortality rate was reduced by 12%.…”
Section: Workflowmentioning
confidence: 99%
“…ID and AST play a major role. Microbial growth in blood culture bottles usually takes 24-48 h. Identification with MALDI-TOF MS can be achieved as soon as 3-4 h after start of subculture [6][7][8]. Numerous studies have shown the performance of MALDI-TOF MS directly from positive blood culture broth with results available within few hours, but have been hampered by a poor accuracy for Gram-positive bacteria [9].…”
Section: Introductionmentioning
confidence: 99%